2017
DOI: 10.2147/jpr.s134636
|View full text |Cite
|
Sign up to set email alerts
|

Persistent cauda equina syndrome after caudal epidural injection under severe spinal stenosis: a case report

Abstract: Caudal epidural injection (CEI) is one of the most common treatments for low-back pain with sciatica. CEI rarely leads to neurologic complications. We report a case of persistent cauda equina syndrome after CEI. A 44-year-old male patient with severe L4 and L5 spinal ste-nosis underwent CEI for low-back pain and sciatica. The CEI solution consisted of bupivacaine, hyaluronidase, triamcinolone acetonide, and normal saline. He experienced motor weakness and sensory loss in both lower extremities and neurogenic b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…The advantage of ESI is that it is minimally invasive for patients with lumbar pain. Significant complications after ESI are rare but can result from mechanical ischemia, direct needle injury, infection, or injection solution [10]. It is likely the ESI in our patient was associated with the acute pancreatitis.…”
Section: Discussionmentioning
confidence: 83%
“…The advantage of ESI is that it is minimally invasive for patients with lumbar pain. Significant complications after ESI are rare but can result from mechanical ischemia, direct needle injury, infection, or injection solution [10]. It is likely the ESI in our patient was associated with the acute pancreatitis.…”
Section: Discussionmentioning
confidence: 83%
“…6 Lumbar spinal stenosis or lumbar disc disease increase risk of neurological complication following neuraxial anesthesia. 7,11 Our patient did not have any history of back pain, numbness or claudication pathognomonic of lumbar spinal stenosis, 3 no history of neurological disorder or neurotoxic drug intake, we performed caudal epidural block without any difficulty and there were no signs of hematoma and abscess.…”
Section: Discussionmentioning
confidence: 95%
“…2) stated that space-occupied lesion formed by injected fluid would make transient neurologic deficit. Seo et al 7) also reported that neurotoxicity came from local anesthetics could induce CES. The patient was left with a permanent neurological deficit despite of emergent surgical treatment.…”
Section: Discussionmentioning
confidence: 98%